Lexical tonal discrimination in Zapotec children. A study of the theta rhythm - Adrián Poblano; Eduardo Castro-Sierra; Carmina Arteaga; Santiago J. Pérez-Ruiz (Permanyer, 2016)
Background: Zapotec is a language used mainly in the state of Oaxaca in Mexico of tonal characteristic; homophone words with difference in fundamental frequency with different meanings. Our objective was to analyze changes in the electroencephalographic (EEG) theta rhythm during word discrimination of lexical tonal bi-syllabic homophone word samples of Zapotec. Methods: We employed electroencephalography analysis during lexical tonal discrimination in 12 healthy subjects 9-16 years of age. Results: We observed an increase in theta relative power between lexical discrimination and at rest eyes-open state in right temporal site. We also observed several significant intra- and inter-hemispheric correlations in several scalp sites, mainly in left fronto-temporal and right temporal areas when subjects were performing lexical discrimination. Conclusions: Our data suggest more engagement of neural networks of the right hemisphere are involved in Zapotec language discrimination.